Clinical learning of nursing students during the COVID-19 pandemic in Limpopo province, South Africa - Linda Nchabeleng; Mamare A. Bopape; Ledile E. Manamela; Tshepo A. Ntho (AOSIS, 2024)
Background: The Nursing Education Programme was affected during the coronavirus disease 2019 (COVID-19) pandemic, resulting in nursing students being unable to participate in the clinical experiential learning required by the South African Nursing Council. Objectives: The study seeks to explore and describe nursing students' experiences of clinical experiential learning during the COVID-19 pandemic. Method: A qualitative, explorative and descriptive, research design was used in the study. A non-probability purposive sampling method was used, and 55 nursing students participated in the study. Data were collected through six focus group discussions, consisting of 8-12 nursing students in each group. Data were analysed following Tesch's open coding method. Results: Three themes emerged from the study's findings: The impact of COVID-19 on the clinical experiential learning of nursing students, the effects of COVID-19 on the mental well-being of nursing students, and nursing students' experiences of support during the COVID-19 pandemic. Notably, 11 sub-themes emerged. Conclusion: The findings of this study reveal that the COVID-19 pandemic severely disrupted the Nursing Education Programme, highlighting the challenges of inadequate clinical hours, restricted clinical access and the significant psychological impact on students. Contribution: This study adds to the literature on students' experiences during clinical experiential learning in South Africa during the COVID-19 pandemic.